Analisis Rantai Usaha Padi (Beras) Merah Di Kabupaten Boyolali - Widiyanti, Emi; Cahyadin, Malik (EP FEB UNS, 2015)
This study aims to analyze the supply chain of red rice in Boyolali District. The supply chain analysis covers parties in the supply chain, internal and external analysis and supply chain model. The research data using primary data with number of respondents about 60 farmers. Methods of analysis are using descriptive-qualitative and SWOT analysis. The results showed that the parties in the supply chain of red rice are a family/farmer, businessman/trader, partner/farmer groups, and their companions of agriculture industry. Meanwhile, internal analysis showed that red rice has a high price and resistant to pests but require a relatively long period of planting. External analysis showed that red rice has a market mainly processed food industry, but the public has not much to like the texture of it. Keywords: red rice, supply chain, SWOTJEL Classification: D24, D47